Knowledge, attitudes, and practices in adult patients and parents of pediatric atopic dermatitis patients: a cross-sectional study - Zhifeng Nie; Zhifeng Nie; Pengyang Fan; Yuting Zhou; Sheng Han; Sheng Han (Frontiers Media S.A., 2024)
ObjectiveTo investigate the knowledge, attitude, and practice (KAP) of adult Atopic Dermatitis patients and parents of pediatric atopic dermatitis patients toward the disease.MethodsA cross-sectional study was conducted from January to February 2022, involving 1,193 Asian Atopic Dermatitis patients from the Atopic Dermatitis patient organization "Atopic Dermatitis Home." The study included 594 adult patients and 599 parents of pediatric atopic dermatitis patients, with self-designed questionnaires assessing general demographics and continuous variables KAP.ResultsAdult patients demonstrated higher knowledge scores, particularly in areas of bathing and skincare (3.64 ± 0.68 vs. 3.35 ± 0.93, p < 0.01), and treatment precautions (3.35 ± 0.93 vs. 3.81 ± 0.51, p < 0.01), compared to parents of pediatric patients. In terms of practices, adult patients scored higher in treatment adherence (0.69 ± 0.96 vs. 3.33 ± 1.19, p < 0.01) and lifestyle management (1.85 ± 0.39 vs. 1.69 ± 0.59, p < 0.01), while parents scored higher in risk avoidance (1.58 ± 0.79 vs. 1.62 ± 0.88, p < 0.01). Regression analysis revealed that knowledge and attitudes significantly positively affected practices. Treatment adherence was positively associated with knowledge of treatment precautions (B = 0.323, 95% CI 0.175, 0.471, p < 0.001) and negatively with disease characteristics (B = -0.112, 95% CI -0.216, −0.008, p = 0.035). Self-treatment was positively associated with knowledge of disease characteristics (B = 0.154, 95% CI 0.036, 0.272, p = 0.011) and medication attitudes (B = 0.282, 95% CI 0.208, 0.356, p < 0.001). Lifestyle management was positively associated with knowledge of skincare (B = 0.071, 95% CI 0.036, 0.106, p < 0.001) and treatment precautions (B = 0.160, 95% CI 0.096, 0.224, p < 0.001), but negatively with patient type (B = -0.127, 95% CI -0.184, −0.070, p < 0.001). Risk avoidance was positively associated with knowledge of skincare (B = 0.128, 95% CI 0.067, 0.189, p < 0.001) and treatment precautions (B = 0.163, 95% CI 0.053, 0.273, p = 0.004).ConclusionThe study concluded that knowledge and attitudes significantly affect health practices among Atopic Dermatitis patients. Enhancing patient education on treatment precautions and skincare can improve adherence and management behaviors, highlighting the need for targeted educational interventions.